5α, 6α-Epoxyphytosterols and 5α, 6α-Epoxycholesterol Increase Nitrosative Stress and Inflammatory Cytokine Production in Rats on Low-Cholesterol Diet. (8th June 2020) - Wielkoszyński, Tomasz; Zalejska-Fiolka, Jolanta; Strzelczyk, Joanna K.; Owczarek, Aleksander J.; Cholewka, Armand; Kokoszczyk, Katarzyna; Stanek, Agata
Abstract : Objective . Oxidized cholesterol derivatives are compounds with proven atherogenic and mutagenic effects. However, little is known about the effect of oxidized plant sterol derivatives (oxyphytosterols), whose structure is similar to the one of oxycholesterols. Our previous studies indicate that they have a similar profile of action, e.g., both exacerbate disorder of lipid metabolism and oxidative stress in experimental animals. The aim of the present study was to assess the effect of epoxycholesterol and epoxyphytosterols (mainly sitosterol) on the severity of nitrosative stress and the concentration of selected proinflammatory cytokines in blood and liver tissue of rats on a low-cholesterol diet. Material and Methods . Forty-five male Wistar rats were fed with feed containing 5 α, 6 α -epoxyphytosterols (ES group, n : 15), 5 α, 6 α -epoxycholesterol (ECh group, n : 15), and oxysterol-free feed (C group, n : 15) for 90 days (daily dose of oxysterols: 10 mg/kg). At the end of the experiment, nitrotyrosine, TNF- α, IL-1 β, IL-6, and lipid metabolism parameters were determined in blood serum. Furthermore, nitrotyrosine, TNF- α, cholesterol, and triglyceride content were determined in liver homogenates. Results . Serum nitrotyrosine, IL-1 β, and TNF- α concentrations as well as TNF- α content in the liver were significantly higher in both groups exposed to oxysterols (ECh and ES groups) as compared to the C group. The serum IL-6 level and nitrotyrosine content in the liver were significantly higher in the ECh group, as compared to the C and ES groups. There was evidence to support the dyslipidemic effect of studied compounds. Conclusions . The results indicate that oxidized plant sterols have a similar toxicity profile to that of oxycholesterols, including nitrosative stress induction, proinflammatory effect, and impaired lipid metabolism.